2012
DOI: 10.1038/srep00835
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the performance of FA, DFA and DMA using different synthetic long-range correlated time series

Abstract: Notwithstanding the significant efforts to develop estimators of long-range correlations (LRC) and to compare their performance, no clear consensus exists on what is the best method and under which conditions. In addition, synthetic tests suggest that the performance of LRC estimators varies when using different generators of LRC time series. Here, we compare the performances of four estimators [Fluctuation Analysis (FA), Detrended Fluctuation Analysis (DFA), Backward Detrending Moving Average (BDMA), and Cent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(113 citation statements)
references
References 60 publications
1
107
0
5
Order By: Relevance
“…Our results have demonstrated that the performance of mth order centered DMA, where m is a nonnegative even integer, is very well comparable with that of (m + 1)th order DFA. It has been demonstrated that the zeroth order centered DMA has a good performance to characterize long-range correlation and fractal scaling behavior [28,34]. In practical applications to real-world time series, the higher detrending power degree would be very important to improve estimation accuracy and to validate the observed scaling behavior [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Our results have demonstrated that the performance of mth order centered DMA, where m is a nonnegative even integer, is very well comparable with that of (m + 1)th order DFA. It has been demonstrated that the zeroth order centered DMA has a good performance to characterize long-range correlation and fractal scaling behavior [28,34]. In practical applications to real-world time series, the higher detrending power degree would be very important to improve estimation accuracy and to validate the observed scaling behavior [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Until now various methods have been developed and applied to characterize the correlation behavior on many time series starting from R/S analysis [4][5][6][7], detrended fluctuation analysis (DFA) [8][9][10], detrended moving average method (DMA) [11], multifractal detrended fluctuation analysis (MFDFA) [12], wavelet based fluctuation analysis (WBFA) [13][14][15][16], average wavelet coefficient method (AWC) [17], wavelet transform modulus maxima (WTMM) [18] etc. These methods have found wide application in the analysis of correlations and characterization of scaling behavior of time-series data in physiology, finance, and natural sciences [19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The MF-DMA family gives better scaling behavior in many cases [9,31]. We intent to perform MF-DMS-based method to compare the presented results obtained with the MF-DFS to get best segmentation results in our next study.…”
Section: Discussionmentioning
confidence: 96%